Longitudinal Fluctuations of National Help-Seeking Reports for Domestic Violence Before, During, and After the Financial Crisis in Cyprus - Kyriakidou, Marilena (Journal of interpersonal violence, 2021)
Although many studies generally agree that unemployment may affect domestic violence, little is known about these effects in small nations. The relationship between unemployment and domestic violence in large and small nations may be different. This is because small nations have more expensive public sectors and limited employment opportunities in comparison with larger nations. We examined how longitudinal rates of national help-seeking domestic violence contacts (DVCs) from the only nongovernmental domestic violence support agency in Cyprus (a small nation) fluctuated in relation to national unemployment data between 1996 and 2016. This period included an economic crisis which commenced in 2011 and showed signs of recovery in 2015. We analyzed whether the fluctuations in unemployment registrations could predict changes in DVCs. Our analysis included 5,103,120 unemployment registrations and 21,774 DVCs. Findings supported our hypothesis and revealed unemployment predicted and correlated with DVCs. There were significant changes to DVCs when Cyprus plunged into economic crisis, meaning that when unemployment increased, DVCs also increased. Cyprus does not deviate from larger societies in help-seeking behavior in the form of people contacting a national helpline when exposed to economic crises. This study provides evidence of the link between economic hardship and increased help-seeking behaviors in small nations. Societies at risk of an economic crisis need to consider the potential impact on domestic violence rates and on demand for support services.